Sistem Informasi Geografis Pencarian Studio Foto Terdekat dan Jalur Terpendek Menggunakan Metode Dijkstra (Studi Kasus Kota Bandar Lampung) - Ir. Machudor Yusman (Universitas Mitra Indonesia, 2020)
AbstractThe very rapid development of information, especially in the internet sector, indirectly facilitates the dissemination of information. One of the information needed by the community is GIS (Geographic Information System) technology, which is a system that is oriented to geographic position and is capable of manipulating, processing and displaying spatial data and attributes. In the city of Bandar Lampung, there are several photo studios scattered at several locations with different facilities and services in each location. However, there are still many who do not know the location and facilities of the Photo Studio and people usually look for a photo studio by asking friends or colleagues. In addition, the search model on Google is inefficient because it will automatically first visit the Google website before finding a location that is sometimes not updated. Therefore, the Geographical Information System is one solution to dealing with the problem by proposing to design a web-based geographic information system for the search for the nearest Photo Studio using the Dijkstra method. The results of the research on the GIS Photo Studio application system have been running well and in accordance with what is expected, where the system can help users find location points on the map, travel routes, distance and travel time.